The complete mitochondrial genome of turnip (Brassica rapa ssp. rapa) - Yanjing Ren (Mitochondrial DNA. Part B. Resources, 2021)
Turnip (Brassica rapa ssp. rapa) is one of the most important leaf and root vegetable crop in the Brassicaceae family. In this study, the complete mitochondrial genome sequence was assembled at the first time and a circle form of 219,736 bp in size was obtained. A total of 99 genes were annotated, including 78 protein-coding genes, 18 transfer RNA (tRNA) genes, and three ribosomal RNA (rRNA) genes. The phylogenetic relationship showed that turnip is closely related to subsp. campestris rather than Raphanus staivus.